2022
DOI: 10.2147/idr.s380137
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Combined with RNA Sequencing to Screen Biomarkers of Sepsis

Abstract: Purpose To screen biomarkers in the serum of patients with sepsis by proteomics combined with RNA sequencing technology, and to find new diagnostic and therapeutic targets for sepsis. Patients and Methods Blood samples of 22 sepsis patients (sepsis group) and 10 healthy volunteers (normal group) were collected from January 2019 to December 2020. Data-independent acquisition (DIA) method was employed for protein profiling, RNA sequencing was employed for gene sequencing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…Considering the life-threating and lacking of effective treatment modality property of sepsis, novel therapeutic targets should be explored using the current integrated bioinformatics analyses [7]. Furthermore, considering the 24-hour SAT was employed as prognostic indicator for sepsis[8], platelet related genes could be served as an intervene for sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the life-threating and lacking of effective treatment modality property of sepsis, novel therapeutic targets should be explored using the current integrated bioinformatics analyses [7]. Furthermore, considering the 24-hour SAT was employed as prognostic indicator for sepsis[8], platelet related genes could be served as an intervene for sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…CELA3A has little elastolytic activity and might play a critical role in intestinal transport and cholesterol metabolism. , We found that CELA3A expression was increased significantly in the drainage fluid of AL patients. With respect to serum levels, although AMY2A, RETN, and CELA3A in serum were correlated with acute pancreatitis, sepsis, and chronic pancreatitis, there is no literature indicating that AMY2A, RETN, and CELA3A in serum were associated with AL in patients who underwent laparoscopic low anterior resection for rectal cancer. Correspondingly, AMY2A, RETN, and CELA3A expression was induced by LPS stimulation.…”
Section: Discussionmentioning
confidence: 98%
“…From the 1312 quantified proteins, RFE-SHAP analysis was able to identify a panel of 18 with high accuracy and separating power that indicates they would provide a good starting point for investigation as potential protein biomarkers. In fact, many of these proteins have already been identified and studied as potential sepsis markers or markers for infection and inflammation 36 45 . The majority of the 18 proteins were higher in abundance in the more severe subphenotype, such as CD44 antigen (CD44), Complement C1r subcomponent-like protein (C1RL), Beta-1,4-galactosyltransferase 1 (B4GT1), and Lipopolysaccharide-binding protein (LBP).…”
Section: Discussionmentioning
confidence: 99%